2022
DOI: 10.3389/fimmu.2022.1080456
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanism of gut microbiota-derived short-chain fatty in the prevention and treatment of diabetic kidney disease

Abstract: Diabetic kidney disease (DKD), an emerging global health issue, is one of the most severe microvascular complications derived from diabetes and a primary pathology contributing to end-stage renal disease. The currently available treatment provides only symptomatic relief and has failed to delay the progression of DKD into chronic kidney disease. Recently, multiple studies have proposed a strong link between intestinal dysbiosis and the occurrence of DKD. The gut microbiota-derived short-chain fatty acids (SCFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 119 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…Research suggests that the gut microbiota may affect DKD development by modulating endocrine functions and the composition of microbial metabolic byproducts within the gut[ 27 ]. Notably, SCFAs derived from the gut microbiota can regulate inflammation, oxidative stress, fibrosis, and energy metabolism, thus offering preventive and therapeutic potential in DKD[ 6 ]. Experimental evidence indicates a notable decrease in DKD incidence in diabetes-induced animals fed a high-fiber diet, emphasizing the potential renoprotective role of DF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that the gut microbiota may affect DKD development by modulating endocrine functions and the composition of microbial metabolic byproducts within the gut[ 27 ]. Notably, SCFAs derived from the gut microbiota can regulate inflammation, oxidative stress, fibrosis, and energy metabolism, thus offering preventive and therapeutic potential in DKD[ 6 ]. Experimental evidence indicates a notable decrease in DKD incidence in diabetes-induced animals fed a high-fiber diet, emphasizing the potential renoprotective role of DF.…”
Section: Discussionmentioning
confidence: 99%
“…DKD markedly increases the risk of cardiovascular events and progression to end-stage renal disease[ 4 , 5 ], culminating in the need for dialysis or renal transplantation. Existing therapeutic approaches offer only symptomatic relief and cannot impede the progression of DKD into chronic kidney disease (CKD)[ 6 ]. Therefore, delaying or ameliorating the onset and progression of DKD is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The human gut microbiota consists of approximately 10 14 microorganisms and plays a crucial role in host function, especially in immunity and metabolism ( Tao et al., 2022 ; Niu and Meng, 2023 ). Many studies demonstrated that the gut microbiota is closely interrelated with GBC progression, but most relative mechanistic studies have primarily focused on bacteria.…”
Section: Bacteria In Gbc Pathogenesismentioning
confidence: 99%
“…In fact, numerous studies have shown that gut microbiota dysbiosis can trigger oxidative stress and play a key role in the pathogenesis of DKD (Fang Q. et al, 2021;Mosterd et al, 2021;Ni et al, 2022;Tao et al, 2022). It has been demonstrated that increased circulating levels of typical gut microbiota-derived uremic toxins, including PCS, IS, PS and TMAO, trigger oxidative stress and increase the production of ROS, which activates NLRP3 inflammasome, leading to inflammation in glomerular endothelial cells and exacerbating renal dysfunction of DKD (Chen et al, 2017;Fang Q. et al, 2021;Huang et al, 2017a;Mosterd et al, 2021;Ni et al, 2022).…”
Section: Gut Microbiota Dysbiosis and Oxidative Stress In Dkdmentioning
confidence: 99%